Penguatan Nilai-Nilai Keagamaan Dalam Rangka Membentuk Perilaku Jujur dan Bertanggung Jawab di Rumah Asuh Yabni Padang - Usman; Devi Syukri Azhari; Ashabul Fadhli (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The value of honesty is an important value that should be taught by every student in school, both through learning in the classroom and outside the classroom. Instilling the value of honesty is intended so that students understand the importance of this value in every aspect of life. Honesty is an important capital for students to become the next generation of the nation in the future. Honesty is one of the most valuable values ​​in life. Fostering and instilling the values ​​of honesty is then carried out in the family environment and must be done as early as possible so that it affects the growth and development of children. Through fostering and instilling the values ​​of honesty in accordance with human values ​​in each individual in the family, a peaceful and prosperous civilization will be created. Because after all education in the family has a strategic value in the formation of a child's personality. since childhood children have received education from both parents through exemplary, honesty, and good daily living habits in the family. Whether or not the example given by parents is good and how the daily living habits of parents in the family will affect the development of the child's soul.